2020
DOI: 10.1016/j.jinf.2020.05.064
|View full text |Cite
|
Sign up to set email alerts
|

A clinical risk score to identify patients with COVID-19 at high risk of critical care admission or death: An observational cohort study

Abstract: Background: The COVID-19 pandemic continues to escalate. There is urgent need to stratify patients. Understanding risk of deterioration will assist in admission and discharge decisions, and help selection for clinical studies to indicate where risk of therapy-related complications is justified. Methods: An observational cohort of patients acutely admitted to two London hospitals with COVID-19 and positive SARS-CoV-2 swab results was assessed. Demographic details, clinical data, comorbidities, blood parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
170
5
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(204 citation statements)
references
References 12 publications
16
170
5
5
Order By: Relevance
“…So far, only a limited number of studies have looked for an association between HLA haplotypes and genetic susceptibility or resistance to SARS coronavirus infection. However, an impact of HLA haplotypes may identify some of the unexplained differences in disease severity and mortality observed across different countries and different population ethnicities (150)(151)(152)(153)(154). Allele typing of 37 probable SARS patients in Taiwan identified an association between HLA-B * 4601 and SARS-CoV infection (155); however, this was not confirmed in a study of 90 serologically confirmed SARS-CoV patients in Hong Kong (156,157).…”
Section: Human Inborn Errors Of Immunity Predisposing To Coronavirusmentioning
confidence: 99%
“…So far, only a limited number of studies have looked for an association between HLA haplotypes and genetic susceptibility or resistance to SARS coronavirus infection. However, an impact of HLA haplotypes may identify some of the unexplained differences in disease severity and mortality observed across different countries and different population ethnicities (150)(151)(152)(153)(154). Allele typing of 37 probable SARS patients in Taiwan identified an association between HLA-B * 4601 and SARS-CoV infection (155); however, this was not confirmed in a study of 90 serologically confirmed SARS-CoV patients in Hong Kong (156,157).…”
Section: Human Inborn Errors Of Immunity Predisposing To Coronavirusmentioning
confidence: 99%
“…Of the 30 models, 23 were trained on patients in China , 2 were trained on patients in the United States 30,31 , and 5 were trained on patients in South Korea 32 or Europe [33][34][35][36] . Only 8 of the models underwent validation on either held-out or external datasets 7,10,14,18,19,24,26,36 , and 1 underwent prospective validation . No model predicted favorable outcomes and no studies reported clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…While several scores have been investigated and further validated for optimal for the management of CAP, for COVID-19 patients drawing a de nite conclusion among the many proposed prognostic biomarkers and scores appears to be very di cult [13][14][15][16][17]. The CALL score and a risk score including several parameters calculated at hospital admission (age, sex, ethnicity, oxygen saturations, radiology, neutrophil count, CRP, albumin, creatinine, comorbidities) were recently developed to predict 28-day mortality and ICU admission [9,16]. Furthermore, a predictive model (named the HNC-LL score and based on neutrophil count, lymphocyte count, LDH level, CRP level and hypertension) was also developed and validated to enable early and accurate identi cation of patients with SARS-CoV-2 infection at a high risk of severe disease [34].…”
Section: Several Studies Have Identi Ed a Close Correlation Between Hmentioning
confidence: 99%
“…Taking into consideration the abovementioned scores, we decided to exclude from our analysis the score proposed by Galloway et al since disease severity was radiologically assessed with adoption of on chest radiograph examination that was replaced by chest CT in our patients population [9]. The HNC-LL score was highly predictive of severe disease, with the de nition of severity including both subjects requiring intensive care and those with respiratory distress but not requiring ICU admission [34].…”
Section: Several Studies Have Identi Ed a Close Correlation Between Hmentioning
confidence: 99%
See 1 more Smart Citation